Assessing the Effect of Service Excellence on Passenger Satisfaction at Regional Airports - Deddy Novie Citra Arta; Muhammad Nur Cahyo Hidayat Nasrullah; Ahmad Raihan Farhan (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes the effect of check-in counter staff service excellence on passenger satisfaction at Sentani International Airport, Papua, Indonesia. The research was motivated by persistent queues and declining comfort during peak hours, indicating that service excellence has not been fully optimized despite existing government and corporate service standards. Methodology/approach: A quantitative descriptive approach was applied using structured questionnaires distributed to 100 passengers. Service excellence was measured through the 6A Model (Ability, Attitude, Appearance, Attention, Action, Accountability), while passenger satisfaction was evaluated through perceived service quality, staff service, airline image, and punctuality. Data were analyzed using SPSS 25.0 with validity, reliability, and classical assumption tests, followed by simple linear regression. Results/findings: Service excellence significantly and positively affected passenger satisfaction (? = 0.589, t = 12.764, p < 0.001, F = 162.89, R² = 0.803). Among the 6A dimensions, attitude (friendliness, politeness, professionalism) scored highest, while action (responsiveness, speed) was lowest. Conclusion: The findings confirm that implementing service excellence at check-in counters is crucial for enhancing passenger satisfaction and strengthening the airport’s image as Papua’s main air transport hub. Practically, improving staff responsiveness and operational efficiency can enhance service perception and foster passenger loyalty. Limitations: The study is limited to Sentani International Airport, and results may vary across airports with different characteristics. Contribution: This study validates the 6A model in a regional airport context and offers insights for PT Angkasa Pura and policymakers to optimize staff performance and passenger experience.